Religious philosophy of Thomas Chubb - Polyakov, Andrey (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. I, Bogoslovie, filosofii͡a, 2022)
The article presents a brief biography of the little-studied British deist Thomas Chubb (1679-1747) and a reconstruction of his ideas about capabilities of human mind. The goal of this article is to study the religious philosophy of T. Chubb that Russian studies does not distinguish from ideas of other deists. That is why the idea of the phenomenon of deism is still less clear in relation to foreign studies. The article analyzes and presents Chubbs concepts about the independence of religious truths from human perception, that are presented in «Discourse concerning Reason, with Regard to Religion and Divine Revelation» (1733) and «An Enquiry into the Ground and Foundation of Religion». The article documents that the English philosopher formulated three "author's" truths of natural religion: there is an initial difference between objects, independent of human perception; this distinction is the basis for human behavior; God made these foundations a moral rule for all people and for himself. The work identifies and analyzes the definition of the phenomenon of "deism" in Chubb's treatises, as well as an assessment of his philosophy in the context of this definition – the natural religion of reason or belief and just and sense of a Deity impressed upon the mind, and is the governing principle of a man’s-affections and actions. The correlation of the ideas of Thomas Chubb and Matthew Tindal is analyzed. At the end of the article, a brief conclusion is made about the place of T. Chubbs philosophy to deism in general. The author of this work believes that despite the absence of references to other deists by the English philosopher, the ideas of this thinker fit into their religious and philosophical system, specifically about the issue of understanding natural religion. The sources of this article are treaties «The Sufficiency of Reason in Matters of Religion, Farther Considered» (1732), «Discourse concerning Reason, with Regard to Religion and Divine Revelation» (1733), «Some reflections upon the comparative excellency and usefulness of moral and positive duties» (1733), «The true Gospel of Jesus Christ Asserted»(1741) and several other treatises.